Modification of the edge wave in shock wave lithotripsy - Zhou, Yufeng. (2013)
To reduce the bubble cavitation and the consequent vascular injury of shock wave lithotripsy (SWL), a new method was devised to modify the diffraction wave generated at the aperture of a Dornier HM-3 lithotripter. Subsequently, the duration of the tensile wave was shortened significantly (3.2±0.54 μs vs. 5.83±0.56 μs). However, the amplitude and duration of the compressive wave of LSW between these two groups as well as the -6 dB beam width and the amplitude of the tensile wave are almost unchanged. The suppression on bubble cavitation was confirmed using the passive cavitation technique. At the lithotripter focus, while 30 shocks can cause rupture of blood vessel phantom using the HM-3 lithotripter at 20 kV; no rupture could be found after 300 shocks with the edge extender. On the other hand, after 200 shocks the HM-3 lithotripter at 20 kV can achieve a stone fragmentation of 50.4±2.0% on plaster-of-Paris stone phantom, which is comparable to that of using the edge extender (46.8±4.1%, p=0.005). Altogether, the modification on the diffraction wave at the lithotripter aperture can significantly reduce the bubble cavitation activities. As a result, potential for vessel rupture in shock wave lithotripsy is expected.